Sustained release tablet of theophylline by hot melt wax coating technology - Padsalgi, Amol; Bidkar, Sanjay; Jadhav, Vijay; Sheladiya, Deepak (Asian Journal of Pharmaceutics (AJP), 2014)
Coating is one of the effective method used for sustaining the release of dosage form. There are various hydrophilic and hydrophilic polymers which are use to sustain the drug release. Waxes are one of the material which can be use to coat the drug in order to control the release. Coating with waxes can be achieved by dissolving it in suitable solvent or by hot melt wax coating. Hot melt coating technique defined as the application of fine layer of coating material in molten state over the substrate. Hot melt coating technique is widely used to coat granules, pellets and tablets in order to sustained the drug release, mask the bitter taste of drug, improve stability etc. Hot melt wax coatings have various advantages over wax solution coating. Toxicity of the organic solvent residues and the influence of environmental protection are major problems associated with solvent coating. The main goal of this study was to study the effect of different coating technique i.e. pan spray method and pan pour method on release pattern of theophylline and also to study the effect of different pore former like sodium laurel sulphate (SLS) and hydroxyl propyl methyl cellulose (HPMC) on release pattern. It was found that pan spray technique is the best technique to control the release due to uniform film formation, while pan pour method showed variation in release of drug from same batch this was due to non uniform coating of tablets and very low coating efficiency. If we compare the effect of pore former it was found that release of drug can be controlled by using suitable concentration of pore former while faster release was seen when SLS was used as a pore former in lower concentration than HPMC.